Analisis Perpindahan Panas dan Laju Kalor Penyebab Cacat Produksi Injection Molding Spakbor Sepeda Motor di PT. XYZ - Dewi Marlina; Kardiman Kardiman; Najmudin Fauji (Jurnal Ilmiah Wahana Pendidikan, 2022)
From observations on molding and die casting companies as well as the production of plastic molding automotive parts, several defects were found in the injection engine results. Types of product defects include short mold, black spot, flowmark and wide flashing. This study aims to suppress the problem of the factors causing product defects, namely by calculating the heat transfer that occurs in the mold and calculating the rate of heat absorbed by the chiller which is expected to reduce product defects on the front fender of the motorcycle so that it can meet the desired production targets and can reduce production costs incurred. excess. The results showed a decrease in the mold temperature of 35°C and the melting temperature of the plastic at 220°C, which was 1.19%. And to maintain a mold temperature of 35°C with a plastic melting temperature of 220°C, the proper chiller temperature setting occurs at 28°C. It can be concluded that the cause of defects in the front fender of a motorcycle is the relationship between the melting temperature of the plastic as a raw material and the temperature of the mold used